Gain-of-Function Mutants of the Cytokinin Receptors AHK2 and AHK3 Regulate Plant Organ Size, Flowering Time and Plant Longevity - Bartrina, Isabel; Jensen, Helen; Novák, Ondřej; Strnad, Miroslav; Werner, Tomáš; Schmülling, Thomas (Plant physiology, 2017)
The phytohormone cytokinin is a regulator of numerous processes in plants. In Arabidopsis (Arabidopsis thaliana), the cytokinin signal is perceived by three membrane-located receptors named ARABIDOPSIS HISTIDINE KINASE2 (AHK2), AHK3, and AHK4/CRE1. How the signal is transmitted across the membrane is an entirely unknown process. The three receptors have been shown to operate mostly in a redundant fashion, and very few specific roles have been attributed to single receptors. Using a forward genetic approach, we isolated constitutively active gain-of-function variants of the AHK2 and AHK3 genes, named repressor of cytokinin deficiency2 (rock2) and rock3, respectively. It is hypothesized that the structural changes caused by these mutations in the sensory and adjacent transmembrane domains emulate the structural changes caused by cytokinin binding, resulting in domain motion propagating the signal across the membrane. Detailed analysis of lines carrying rock2 and rock3 alleles revealed how plants respond to locally enhanced cytokinin signaling. Early flowering time, a prolonged reproductive growth phase, and, thereby, increased seed yield suggest that cytokinin regulates various aspects of reproductive growth. In particular, it counteracts the global proliferative arrest, a correlative inhibition of maternal growth by seeds, an as yet unknown activity of the hormone.
Keywords: proteiny huseníčku; mutace; Arabidopsis; Reproduction; signální transdukce; regulátory růstu rostlin; Sequence Homology, Amino Acid; Amino Acid Sequence; Arabidopsis Proteins; květy; meristém; polymerázová řetězová reakce s reverzní transkripcí; sekvenční homologie aminokyselin; histidinkinasa; Cytokinins; regulace genové exprese u rostlin; rozmnožování; Signal Transduction; Time Factors; Meristem; cytokininy; Plants, Genetically Modified; Flowers; Plant Growth Regulators; Gene Expression Regulation, Plant; Microscopy, Electron, Scanning; časové faktory; Reverse Transcriptase Polymerase Chain Reaction; sekvence aminokyselin; geneticky modifikované rostliny; Mutation; mikroskopie elektronová rastrovací; Histidine Kinase